Effects of Vitamin E on Bone Biomechanical and Histomorphometric Parameters in Ovariectomized Rats - Feresin, Rafaela G.; Johnson, Sarah A.; Elam, Marcus L.; Kim, Jeong-Su; Khalil, Dania A.; Lucas, Edralin A.; Smith, Brenda J.; Payton, Mark E.; Akhter, Mohammed P.; Arjmandi, Bahram H. (Journal of osteoporosis, 2013)
The present study examined the dose-dependent effect of vitamin E in reversing bone loss in ovariectomized (Ovx) rats. Sprague-Dawley rats were either Sham-operated (Sham) or Ovx and fed control diet for 120 days to lose bone. Subsequently, rats were divided into 5 groups (n=12/group): Sham, Ovx-control, low dose (Ovx + 300 mg/kg diet; LD), medium dose (Ovx + 525 mg/kg diet; MD), and high dose (Ovx + 750 mg/kg diet; HD) of vitamin E and sacrificed after 100 days. Animals receiving MD and HD of vitamin E had increased serum alkaline phosphatase compared to the Ovx-control group. Bone histomorphometry analysis indicated a decrease in bone resorption as well as increased bone formation and mineralization in the Ovx groups supplemented with MD and HD of vitamin E. Microcomputed tomography findings indicated no effects of vitamin E on trabecular bone of fifth lumbar vertebrae. Animals receiving HD of vitamin E had enhanced fourth lumbar vertebra quality as evidenced by improved ultimate and yield load and stress when compared to Ovx-control group. These findings demonstrate that vitamin E improves bone quality, attenuates bone resorption, and enhances the rate of bone formation while being unable to restore bone density and trabecular bone structure.